Prevalence and risk factors of endocrine disorder in childhood brain tumor survivors: a single- centre study - Ramezan, Nurul Wahidah (2023)
Objective: We aimed to study the prevalence and risk factors of endocrine disorder in childhood brain tumor survivors. Methodology: This study took place at Hospital USM and recruited 124 childhood brain tumor survivors from January 2002 till December 2017. We included brain tumor survivors, 18 years old or younger with either stable disease or in remission and survived for at least 2 years after diagnosis. Demographic data (age at diagnosis, gender, ethnicity, socioeconomic status), clinical clues for endocrine disorders, anthropometrics (weight, height, midparental height), pubertal stage according to Tanner staging, tumor-related characteristics, treatment modalities and endocrine laboratory measurements at diagnosis and during follow up. Logistic regression was applied to evaluate risk factors of endocrine disorder in childhood brain tumor survivors. Results: The prevalence of endocrine disorders in childhood brain tumor survivors was 62.1%. The risk factors were high BMI [adjusted odds ratio (OR) 1.29 , 95% CI: 1.12 to 1.5] , high risk site [adjusted odds ratio (OR) 7.15, 95% CI: 1.41 to 36.3] dan chemotherapy [adjusted odds ratio (OR) 0.18 , 95% CI: 0.05 to 0.62]. Conclusion: The prevalence of endocrine disorders in childhood brain tumor survivors in our centre was 62.1%. The significant risk factors were high BMI, tumor location (suprasellar and intrasellar) and chemotherapy.